A new type of biocompatible fluorescent probe AFN for fixed and live cell imaging of intracellular lipid droplets. Issue 1 (3rd November 2015) - Sharma, Ashutosh; Umar, Shahida; Kar, Parmita; Singh, Kavita; Sachdev, Monika; Goel, Atul
Abstract : We discovered a new type of nontoxic, highly fluorogenic and biocompatible probe AFN for selective staining of intracellular Lipid Droplets (LDs) in both fixed and live human cervical cancer cells (HeLa) and 3T3-L1 pre-adipocytes without any background artifacts. Abstract : We discovered a new class of nontoxic, highly fluorogenic and biocompatible probe AFN for selective staining of intracellular Lipid Droplets (LDs) in both fixed and live human cervical cancer cells (HeLa) and 3T3-L1 pre-adipocytes without any background artifacts. The salient features of the probe are its visible excitation maximum, aqueous compatibility, selectivity and remarkable stability (for more than a week) in live cells, even better than commercially available Nile red.